The Relationship Between Workload And Psychological Well-Being Among Academicians In Selected Tvet Institution - Nur Lina, Nor Azman (Universiti Malaysia Sarawak (UNIMAS), 2020)
The purpose of this study is to examine the relationship between workload and psychological wellbeing among academicians in selected TVET institution. This study was conducted using quantitative methods and the research instrument used is a questionnaire. The data was obtained from 100 respondents in one of the polytechnics in Kuching, Sarawak. The data was then evaluated using both descriptive and inferential statistics. In addition, the Pearson Correlation Analysis test was used to assess the relationship between independent variables and dependent variables. The findings have shown that it can be confirmed that workload of component which is job demand has no significant relationship with psychological well-being among TVET academicians. However, working hours and task schedule was reported to have a significant relationship with psychological well-being among TVET academicians. The findings of this study may provide useful information and body of knowledge for both practitioners and future researchers for the purpose of improving current policy on work-life balance.